Contemporary inter-hospital transfer patterns for the management of acute coronary syndrome patients: Findings from the EPICOR study. Issue 3 (June 2015) - Sinnaeve, Peter R; Zeymer, Uwe; Bueno, Héctor; Danchin, Nicolas; Medina, Jesús; Sánchez-Covisa, Joaquín; Licour, Muriel; Annemans, Lieven; Jukema, J Wouter; Pocock, Stuart; Storey, Robert F; Van de Werf, Frans
Aim: The EPICOR observational study was designed to describe antithrombotic strategies in a broad acute coronary syndrome (ACS) population; it also included information on inter-hospital transfers and institutional resources. Methods and results: EPICOR enrolled 10, 568 consecutively discharged patients with ST-elevation (STE) or non-STE (NSTE) ACS in 555 centres in 20 countries across Europe and Latin America. Patients were categorized as non-transferred, transferred in from another hospital and then discharged, or transferred out to a second hospital but discharged from their initial hospital after transfer back. Two-thirds of ACS patients were non-transferred, of which only 14% were hospitalized at a centre without a catheterization laboratory, and one-third were transferred in or transferred out. Almost all transferred out patients were transferred out to a hospital with catheterization facilities, most often for primary/urgent/rescue (78%) or planned catheterization (18%) in STE myocardial infarction (STEMI), and primary/urgent/rescue (44%) or planned (43%) catheterization in NSTE-ACS. Transferred in patients were more likely to have a STEMI (60%) than non-transferred (44%) and transferred out patients (36%). In STEMI patients, time from symptom onset to catheterization was shorter in non-transferred patients (median 3.5 h vs . 5.9 h for transferred in and 6.3 h for transferred out). In NSTE-ACS, cardiac markers were positive in 66% of non-transferred patients versus 78% and 82% in transferred in and transferred out, respectively. Conclusions: The lack of on-site 24/7 facilities or the availability of more advanced care are frequent reasons for inter-hospital transfer in ACS. Further follow-up of these patients will help to determine whether these practice patterns affect outcome.